O deslocamento da pedagogia da qualificação profissional para a pedagogia das competências no mundo do trabalho - Rego, Thaís Cristina Figueiredo (2011)
This article has the objective of analyze points related to displacement of professional qualification pedagogy to the competence pedagogy in the work world, as from the productive restructuration speeded up in the 90‟s of the 20th century. Besides it, the intention is to indicate the professional requisites that shall become required from the worker and result in the requirement of a new profile of this professional. The theoretical referential proposed seeks to reflect how the professional formation suits to the necessities brought by the flexibility when it comes to work, articulating theory and practice in the worker formation so it becomes multifunctional, overpowering a group of knowledge and competences and adapting to the flexibility required by the work market. It‟s believed that the organizational technologies, based on flexibility criteria and production integration, need multifunctional workers, capable to keep high productivity levels, mainly in situations that can change very fast. While the professional education model based on qualification leads to a fragmented work evolution, with predetermined tasks the model based on competences proposes the work relationships to become more flexible and independent, this way the worker can overpower the knowledge of the whole production process and not only parts.